THE PREVALENCE OF NEOPLASMS IN MEN: A DETAILED ANALYSIS OF THE MAIN CAUSES, RISK FACTORS AND TREATMENTS - Roque, Vera Lúcia Rodrigues (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Neoplasms are a serious public health problem and the second leading cause of death worldwide. Among the male population, the prevalence of these tumours has increased significantly in recent years. In view of this, the aim of this article is to carry out a detailed analysis of the main causes, risk factors and treatments for neoplasms in men. To achieve this objective, a bibliographical survey was carried out, based on scientific articles, books and official documents on the subject. The methodology used was a systematic literature review, selecting studies that addressed epidemiological data, causes and risk factors of neoplasms in men. The results of this research showed that the main types of neoplasms affecting men are prostate, lung, colon and stomach cancer. Among the most common risk factors for developing these tumours are advanced age, smoking, excessive alcohol consumption, obesity, exposure to chemical agents and genetics. With regard to treatment, there are various options available, with surgery, chemotherapy and radiotherapy being the most commonly used. However, each type of neoplasm requires a specific treatment, depending on the stage and characteristics of the tumour. Therefore, given the prevalence of neoplasms in men, it is essential to raise awareness of the importance of prevention and early diagnosis. In addition, it is necessary to invest in public health policies aimed at educating the population and providing access to information and treatment in order to reduce the incidence of these diseases and improve patients' quality of life.